Assistance for individualized education programs for children with special needs at special education schools in Kuningan Regency - Oom Sitti Homdijah; Rina Maryanti; Budi Susetyo; Euis Heryati; Een Ratnengsih; Nita Nitia Intan Tanbrin (Himpunan Pengembang Kurikulum Indonesia, 2026)
An Individualized Education Program (IEP) is an essential framework that teachers must develop prior to instructing students, particularly those with special needs. An effective IEP is formulated based on assessment results to ensure it is tailored to the student's specific needs. This study aims to investigate the implementation of assistance in developing assessment-based individualized education programs for children with special needs at Sekolah Luar Biasa (SLB) in Kuningan Regency. Data collection was conducted during community service activities targeting SLB teachers in the region. The research employed a mixed-methods approach, combining field studies with the analysis of data from the program's implementation. Results indicate that the assessment-based IEP assistance provided in Kuningan Regency significantly enhanced teachers' understanding and skills in designing such programs. This improvement is evidenced by increases in pre-test and post-test scores, as well as by the quality of the portfolios produced during the assignments. Abstrak Program Pembelajaran Individual (PPI) merupakan suatu hal penting yang harus dibuat oleh para guru sebelum membelajarkan muridnya, khususnya bagi murid berkebutuhan khusus. PPI yang efektif dibuat berdasarkan analisis hasil asesmen agar dapat disesuaikan dengan kebutuhan murid. Penelitian ini memiliki tujuan untuk mengetahui bagaimana pendampingan program pembelajaran individual bagi anak berkebutuhan khusus di SLB Kabupaten Kuningan. Aktivitas pemerolehan data penelitian ini dilakukan pada kegiatan pengabdian kepada masyarakat dengan sasaran para guru Sekolah Luar Biasa (SLB) di Kabupaten Kuningan. Metode penelitian yang digunakan adalah metode campuran dengan melakukan studi lapangan dan mengolah data hasil implementasi pendampingan program. Hasil penelitian menunjukkan pendampingan PPI berdasarkan asesmen bagi anak berkebutuhan khusus di SLB Kabupaten Kuningan memiliki dampak positif terhadap peningkatan pemahaman dan keterampilan guru dalam membuat program pembelajaran tersebut. Hal ini dapat dilihat dari hasil pretest dan post-test serta karya atau portofolio hasil penugasan yang mengalami peningkatan. Kata Kunci: anak berkebutuhan khusus; asesmen; PPI; program pembelajaran individual; sekolah luar biasa